Corporate Identity, Reputation, And Satisfaction as Determinants of Student Study Persistence (Case in One Private University) - Imam Nuraryo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study aims to analyze the impact of corporate identity on student retention and satisfaction at the one of private university in North Jakarta, with corporate reputation serving as a mediating variable. The research framework is based on the Information Integration Theory and Behavior Change Theory as applied frameworks. Swails’ model is useful for explaining the process of student resilience and illustrating the balance between students' internal resources and the institutional support provided by the university This study employs an explanatory survey approach, aiming to understand the reasons for a condition or the factors influencing an event. The population of this study was all new undergraduate students entering the undergraduate program in a private university in North Jakarta. The findings reveal that corporate identity has a direct but modest influence on student retention. it is recommended that private universities continue to improve the quality of their human resources, both in terms of services (including teaching) and facilities However, corporate identity significantly affects corporate reputation. Additionally, corporate identity influences student satisfaction. Corporate reputation strongly affects student satisfaction and also contributes to student retention. Lastly, student satisfaction moderately impacts student retention.